Application of Recitation Method on PPKn Learning to Improve Student Learning Outcome - Dada Suhaida (AL-ISHLAH: Jurnal Pendidikan, 2022)
Specifically, the purpose of this research was to explore information, regarding the implementation of the Recitation Method in Civics learning on 10th IPS1 grade students, and improving students’ learning outcomes on 10th IPS1 grade students by applying the Recitation Method. This research used classroom action research method, conducted in two cycles, each cycle consist of one meeting. The research subjects were the students of 10th IPS1 grade students  of SMA Negeri 4 Kubu Raya with simple random sampling technique. The research data collection used were observation sheets, objective tests and material summary assignments. Observation sheets used to collect data on the application of the Recitation Method in Civics learning, assignment assessment results sheets and objective tests also used to collect data on students’ learning outcomes. The research data was processed by using descriptive statistics. The results shows improvements in students’ learning outcomes by applying the Recitation Method in the percentage of 25%, based from the learning outcomes results of students who had met the Minimum Achievement Criteria. Therefore, the Recitation Method is able to be used as an effective solution for teachers in improving student learning outcomes.